Association of Presence and Severity of Thrombocytopenia with Types and Severity of Malaria - Imran , Muhammad; Badshah , Aliena; Naeem, Hammad; Ahmad , Zeeshan; Ahmed, Khaqan; Shah, Syed Junaid (Indus Journal of Bioscience Research, 2025)
Malaria is a significant community health problem in affected areas such as Pakistan, the most prevalent causing parasitic species being Plasmodium vivax and Plasmodium falciparum. Very common hematological symptoms include thrombocytopenia, which is often seen in the two species. This cross-sectional research paper set out to establish the prevalence and degree of thrombocytopenia in malaria sufferers as well as evaluating the relationship with Plasmodium species. The study was completed in six months at Khyber Teaching Hospital, Peshawar and involved 85 microscopical-confirmed malaria cases. Platelet count (per microliter) was recorded and subdivided according to mild (50,001-150,000/ uL, moderate (20,000- 50,000/ uL) and severe (<20,000/uL) levels of thrombocytopenia. In general, thrombocytopenia was recorded in 70.6 percent of patients, and there were equal proportions of mild, moderate, and severe categories. The prevalence of P. vivax (60%) was much higher than P. falciparum (40%). The frequency of thrombocytopenia was higher in P. vivax (76.5 versus 61.8 per cent) but not significantly different (p = 0.128). P. falciparum cases had a higher frequency of severe thrombocytopenia (29.4%), which suggests that there may be a trend towards increased destruction of platelets during falciparum infections. Although the results did not show any significant association, the high prevalence of thrombocytopenia points to the potential of this lab marker as an early predictor of malaria in malaria-endemic areas, where delay of diagnosis is prevalent. These results justify the practice of assessing the platelet count among febrile individuals who live in endemic areas to develop malaria suspicion early and work on it aggressively. Molecular diagnostics and a larger sample size should be considered in further studies in order to shed more light on species-specific thrombocytopenia patterns.